2020
DOI: 10.1186/s41927-020-0115-2
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilization and costs associated with inflammatory bowel disease among patients with chronic inflammatory diseases: a retrospective cohort study

Abstract: Background: Chronic inflammatory diseases (CIDs; ankylosing spondylitis [AS], psoriatic arthritis [PsA], psoriasis [PsO], or rheumatoid arthritis [RA]) and inflammatory bowel disease (IBD; Crohn's disease and ulcerative colitis) are associated with substantial economic burden. The relative increased costs among patients with CIDs and concomitant IBD compared to those without IBD is an important consideration when deciding on the clinical management of patient symptoms. Given the increasing use of novel agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Finally, our study showed that patients who were admitted with DKA and IBD had a longer length of hospital stay and higher COC. These values of higher healthcare resources utilization correlate favorably with previous evidence from Hudesman et al [ 34 ], and are explained by the increased requirement of therapeutic measures and specialty services for patients with IBD, as a result of the well-known relation between IBD and other comorbid pathologies which make the management of the DKA more complicated, mandating an increase in both lengths of hospital and COC.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, our study showed that patients who were admitted with DKA and IBD had a longer length of hospital stay and higher COC. These values of higher healthcare resources utilization correlate favorably with previous evidence from Hudesman et al [ 34 ], and are explained by the increased requirement of therapeutic measures and specialty services for patients with IBD, as a result of the well-known relation between IBD and other comorbid pathologies which make the management of the DKA more complicated, mandating an increase in both lengths of hospital and COC.…”
Section: Discussionsupporting
confidence: 81%
“…15 International studies reported colectomies in 7%-10% of patients with UC, with decreasing colectomy rates over recent years. [16][17][18] Active UC is associated with reduced health-related quality of life (HRQoL) and productivity, [19][20][21][22][23][24] frequent visits to accident and emergency departments (A&E), hospital stays and healthcare costs, [24][25][26] with greater costs with increasing frequency of relapse. 27 Although colectomy may be life-saving, it was recommended not to be considered a cure for UC.…”
Section: Key Messagesmentioning
confidence: 99%
“…IBD has become a global disease with an accelerating incidence in newly industrialized countries 2 . Characterized by a relapsing and remitting course, patients with IBD need close monitoring and therapy adjustment for an optimal disease management, which requires high health‐care resource utilization and costs 3 . However, the impact of such unprecedented situation of COVID‐19 outbreak on health care of patients with IBD in real‐world setting has seldom been investigated.…”
Section: Introductionmentioning
confidence: 99%